If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 7 = 7x + -3 Reorder the terms: 7 + 8x = 7x + -3 Reorder the terms: 7 + 8x = -3 + 7x Solving 7 + 8x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + 8x + -7x = -3 + 7x + -7x Combine like terms: 8x + -7x = 1x 7 + 1x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + 1x = -3 + 0 7 + 1x = -3 Add '-7' to each side of the equation. 7 + -7 + 1x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -3 + -7 1x = -3 + -7 Combine like terms: -3 + -7 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| W-(-322)=-728 | | 10x^5/2x^2 | | 4a+17=a+13 | | x+(x+1)=1.23 | | x^2+93=93 | | x+432=228 | | x+.25x=1500 | | 180/1(2/15=x/180) | | x^2+11x+121=x+96 | | X+.04x=750000 | | -3x-24=2x+1 | | b-12=2b-4 | | 30=7t-5 | | 6+y=31 | | p^2+13p-30=0 | | 3x^2+3x-18= | | 26=2*3+b | | 35-8v=4(v-1)+13 | | y=-16t^2+120t+10 | | 5x-3=7x-12 | | 3/5x-10=1/6 | | 7m-4m+1=16 | | 3(x-1/4)=5(x/2-1/4 | | 12/7=3/x | | 10v^2-13v-3= | | 4*(-6)=30+x | | 2v^2+v-6= | | 4[7-(-7x-3)]=112x+76 | | 1+32x=11x+7 | | -5+3x=2 | | -3p+24p=6 | | 2x-8=4x+10 |